NUTRITIONAL REQUIREMENTS OF LACTOBACILLUS 30a FOR GROWTH AND HISTIDINE DECARBOXYLASE PRODUCTION - Guirard, Beverly M. (1964)
Guirard, Beverly M. (University of California, Berkeley), and Esmond E. Snell. Nutritional requirements of Lactobacillus 30a for growth and histidine decarboxylase production. J. Bacteriol. 87:370–376. 1964.—The nutritional requirements of Lactobacillus 30a include each of the naturally occurring amino acids, several B vitamins, ascorbic acid, glucose, acetate, and oleate. The nutritional requirements for optimal histidine decarboxylase production (up to 900 μliters of CO(2) per hr per mg of cells) differ to some extent from those for optimal growth. Wholly synthetic and partially defined media are described which produce high enzyme activity, together with rapid and luxuriant growth.